Optimization Of Production Management Based On Swot Analysis In Umkm Development In Indonesia - Muhammad Akhsan Tenrisau; Nur Alam Umar; Muhammad Ridwan Mukhlis; Reski Amalia (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2025)
The purpose of this study is to analyze and describe the optimization of UMKM production management in Indonesia using SWOT analysis as an alternative in developing UMKM. The type of qualitative research with a literature study approach, using lean manufacturing as a supporting theory. Data collection techniques with documentation studies. Data processing techniques with reduction, data presentation, and drawing conclusions. Data validity techniques through source triangulation. The results of the study indicate that production management has an important role in UMKM. Optimization of production management can be done by implementing management functions, including planning, organizing, supervising, and controlling functions. In addition, an important role in production management is in the management of raw material inventory which must have planning, including cost planning, raw material procurement schedules, and raw material distribution. Then, for the development of UMKM in Indonesia, it is done by creating a business strategy through the application of SWOT analysis, so that business actors can easily identify threats and business opportunities from outside, so that there is an opportunity to think about solutions and overcome them, not only that business actors can take advantage of opportunities and increase business strength through SWOT analysis.